2005
DOI: 10.1111/j.1745-7254.2005.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3 expression by siRNA suppresses growth and induces apoptosis in laryngeal cancer cells

Abstract: Aim: To determine the inhibitory effect of the synthetic STAT3 siRNA on the expression of STAT3 gene in human laryngeal cancer cell lines Hep2 and to investigate the effect of STAT3 siRNA on growth and apoptosis in Hep2 cells. Methods: A pair of DNA templates coding siRNA against STAT3-mRNA was synthesized to reconstruct plasmid of pSilencer1.0-U6 siRNA-STAT3. Hep2 cells were transfected with RPMI-1640 media (untreated), plasmid (empty), and STAT3 siRNA, respectively. Northern blot and Western blot analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 28 publications
(45 reference statements)
2
40
0
Order By: Relevance
“…Late apoptotic cells were stained orange and showed condensed and fragmented nuclei. 23 These results suggested that TIMP-3 had not only an effect on induction of early apoptosis, but also late apoptosis in these cells. Moreover, flow cytometry analysis showed that the rate of apoptosis in the TIMP-3 overexpression group was significantly higher than that in the untreated PC-3M cells and the vector-treated PC-3M cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Late apoptotic cells were stained orange and showed condensed and fragmented nuclei. 23 These results suggested that TIMP-3 had not only an effect on induction of early apoptosis, but also late apoptosis in these cells. Moreover, flow cytometry analysis showed that the rate of apoptosis in the TIMP-3 overexpression group was significantly higher than that in the untreated PC-3M cells and the vector-treated PC-3M cells.…”
Section: Discussionmentioning
confidence: 59%
“…31 In China, most prostate cancers are diagnosed in an advanced stage when there is little chance of cure by radical prostatectomy. 23,[32][33][34] Thus, it has become important to develop new treatment strategies for metastasic prostate cancer. 35 Invasion and metastasis of tumors cells, including prostate cancer cells, is dependent on their ability to destroy the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotides containing short hairpin RNA (shRNA) sequences for the target genes of interest were used: C/EBPĪ²-C1 sense -5'-GAAGACCGTGGACAAGCAC-3', 13 STAT3-Gh1 sense -5'-GCAGCAGCTGA ACAACATGT-3', 14 mammalian target of rapamycin (mTOR) sense -5'-GGAGTCTACTCGCTTC-TAT-3'; and AKT sense -5'-GGGCACTTTCGGCAAGG TG-3'. 15 Oligonucleotides were cloned into the H1 promoter driven vector pSuper (Oligoengine, Seattle, WA, USA) as described previously.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…RNAi specific to STAT3 resulted in inhibition of DU-145 prostate cancer cell line by inducing apoptotic cell death (Lee et al, 2004). STAT3 siRNA inhibited the growth of Hep2 human laryngeal cancer cell line, resulting in apoptosis and down regulation of Bcl-2 expression (Gao et al, 2005).…”
Section: Rnai In Tumorigenesismentioning
confidence: 98%